O retorno dos anônimos em “Passado próximo”, de Primo Levi - Almeida, Elaine da Silva Alves de (2025)
This research lies at the intersection of memory and fiction, testimony and literary imagination, focusing on the twelve stories in the section “Passato prossimo” from Primo Levi's book Lilit ed altri racconti. Amidst critical reception that favors his testimonial works, the fictional dimension of his production often remains on the margins. However, it is precisely these stories, constructed in the shadow of the Lager experience, that open space for a profound reflection on what it means to remember, to give form and words to that which often could not be said. The motivation for this investigation thus arises from a paradox: how can fiction become a legitimate and powerful means of remembering the traumatic past? To what extent does it allow the return of silenced voices, of anonymous figures who did not survive or who were never able to testify? Far from opposing testimony, the fictionalization in “Passato prossimo” reveals itself as a form of listening, reworking, and transmission that is anchored in an ethical commitment to the memory of others. Through a bibliographic and interdisciplinary approach that intertwines literature, history, and critical theory, this research draws on contributions from Walter Benjamin (1994), Giorgio Agamben (2008), Régine Robin (2016), Márcio Seligmann-Silva (2003, 2010, and 2022), Beatriz Sarlo (2007), and Jeanne Marie Gagnebin (2018), among others, to reflect on the ethical implications of representing the unrepresentable. The analysis of the stories is guided by five thematic axes—life and survival in the Lager, dehumanization and loss of identity, solidarity and mutual aid, memory and the need to bear witness, language as a tool for survival—which illuminate the narrative strategies with which Levi constructs a literary language capable of giving form to absence. What emerges from this reading is the perception that fiction, far from being a distortion or deviation from historical truth, becomes a unique way of dealing with the memory of trauma. By offering a language to what escaped official records, Levi not only restores humanity to the forgotten figures of history, but proposes a Benjaminian rewriting of memory, where each rescued fragment defies erasure and resists oblivion. Thus, “Passato prossimo” asserts itself as a work that, by fictionalizing testimony, fulfills an ethical duty: to keep alive the memory of those who could not speak and to call us, even today, to listen.